Flood Disaster Mitigation Strategy due to Land Cover Change in Kalijompo Sub-watershed - Kartikasari, Adelia Nur Isna; Muttaqin, Dai Agus; Derka, Icha Tatrisya; Pranantya, Vanadani; Robbani, Hilma Wasilah (Fakultas Teknik, Universitas Brawijaya, 2025)
Kalijompo sub-watershed is included in the Bedadung watershed of Jember Regency. Bedadung watershed is the largest watershed in Jember, and it has a land cover change. One of the factors influencing land cover change is forest fires, which cause a significant reduction in forest area. The significantly reduced forest area will impact increasing river discharge and result in flooding downstream. The downstream of Kalijompo is located in the city center of Jember, which has a dense residential area. Therefore, it is necessary to conduct a flood mitigation strategy. This research aims to assess flood risk and ideal land cover management so that this research can be used as a basis for designing flood disaster mitigation strategies due to land use change. The Soil Water Assessment Tool application models the flood response to land cover and determines sub-watersheds that contribute highly to watershed damage. The flood response model was used as the basis for simulation by creating several land cover scenarios to find the appropriate and optimal land use. Flood risk assessment was obtained by combining the components of flood hazard and vulnerability. Flood mitigation strategies were derived from the land use scenarios complemented by Strengths, Weaknesses, Opportunities, and Threats analysis to identify various factors. The results showed that Kalijompo contributed significantly to watershed damage, and 21.93% of the Kalijompo area was at a high flood risk level. One of the mitigation strategies is managing forest land use, which should be 30% of the total Bedadung watershed area.